Education and specialized training: Ways to increase performance in agriculture - Ancuţa Marin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
This paper makes a brief analysis of education in general and of agricultural profile in particular, and highlights existing problems, and the ways to improve them, in order to increase performances in agriculture. The economic development of a country requires transformations qualitative, quantitative and structural, both in economy and how people think. Therefore, there can be no economic development without fulfilling social conditions without changing the institutional framework, without research and education, without technical progress. On Measure the economic development, educational institutions suffer changes of functions, adapting to specific needs of the moment. In traditional societies, education refers to the transmission and reception of knowledge, to the formation of a public opinion, to maintain a broad social consensus. In modern society, the educational institution acquires a special importance, which can be regarded as recruitment agent and the distribution of individuals or group of individuals to different economic roles or positions within the social structure. Because of this, both in developed countries as well as in emerging the education became a variable of profound influence on progress of human society by facilitating economic development.
Keywords: 330; education; performance; economic development; professional training